Pengaruh Struktur Modal, Kepemilikan Institusional dan Perputaran Modal Kerja Terhadap Nilai Perusahaan: Studi Keuangan pada Sub Sektor Asuransi yang Terdaftar di BEI Periode 2018-2023 - Najma Alifia; Dicky Jhoansyah; Sopyan Saori (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study was to determine how much influence Capital Structure, Institutional Ownership and Working Capital Turnover have on Company Value in the Insurance Sub-Sector listed on the IDX for the 2018-2023 Period. The objects in this study are Capital Structure (X1), Institutional Ownership (X2), Working Capital Turnover (X3) and Company Value (Y). This research uses descriptive and associative methods with a quantitative approach. The sampling technique used in this study used a non-probability sampling approach with a purposive sampling approach. The data analysis techniques used are correlation coefficient test, determination coefficient, multiple linear regression test, simultaneous test (F test) and partial test (t test). Based on the results of the study, it shows that there is a variable relationship between Capital Structure, Institutional Ownership, and Working Capital Turnover on Firm Value of 0.472 which means that the level of relationship between Capital Structure, Institutional Ownership, and Working Capital Turnover on Firm Value includes moderate relationship criteria. Then the results of the partial test show that Capital Structure has a negative and insignificant effect on Firm Value, Institutional Ownership has a positive and significant effect on Firm Value, and Working Capital Turnover has a positive and significant effect on Firm Value. Keywords: Capital Structure, Institutional Ownership, Working Capital Turnover, Company Value.